Abandoned Refugee Vehicles “In the Middle of Nowhere”: Reflections on the Global Refugee Crisis from the Northern Margins of Europe - Seitsonen, Oula Ilari; Herva, Vesa-Pekka; Kunnari, Mika (Journal of Contemporary Archaeology, 2017)
Vehicles abandoned by multinational refugees during the winter 2015–2016 in northern Finnish Lapland’s border checkpoints represent an offshoot of the ongoing global refugee crisis on the so-called “Arctic Route” to Europe via Russia. In the summer 2016 this material reminder of refugee mobility vanished almost totally, as the vehicles were auctioned in a show for promoting Lapland tourism. This photo-essay highlights and discusses some of the manifold aspects connected to this flow of refugees, including, for instance, the ethical concerns of trivializing refugee issues intertwined with a host of global larger-scale matters, or using their material heritage for stimulating recreational mobility in these marginalized northern regions.